Influence of temperature and air flow velocity on the physical and sensory characteristics of tomato (Lycopersicum Esculentum) dehydrated in tray dryer - Palacios Flores, Roberto Antonio (2019)
The main objective was to evaluate the influence of the temperature and velocity of air in the time of dehydration. The raw material was characterized based on the norms of the AOAC, reporting 94,5% of humidity, 3,94 pH; 4,5 ° Brix and 0,93% titratable acidity expressed in citric acid. The dehydration process was carried out with temperatures of 55, 65 and 75 °c at speeds of 0,6; 0,9 and 1,2 m/s, the tomato slices of 5 ± 0,2 mm thick; They underwent a pre-treatment in a solution of sodium metabisulfite to 0,2 % + calcium chloride at 1%, where at the highest temperature the dehydration process culminated in 7 h, while at the lowest temperature dehydrate in 13 h. The percentage of shrinkage of tomato slices was between 18,02 – 28,81. Sensory evaluations carried out with evidence of acceptance by untrained panelists resulted in statistically significant differences in odor, texture and appearance characteristics but not in the characteristic color of the dehydrated samples at 95% confidence.